Shifting global leadership in the world steel industry - Noh, Sang-Chul (KDI School, 1998)
Since the world steel industry began to develop in England, global leadership in the world steel industry shifted from England to the United States and then to Japan in the late 1970s. The development of steel industry and evolution of international competitiveness are influenced by several factors in the U.S. and Japanese steel industry, which provide an interesting case study for examining the key success factors as well as failure factors. In this regard, the purpose of my thesis is to find out what factors caused the shift of world leadership in the steel industry by analyzing of the case of the U.S. and Japanese steel industry. This thesis explores the major factors that resulted in the decline of the U.S. steel industry and contributed to the rise of the Japanese steel industry including the rise of NSC as the world''s largest steel producer. This case study regarding the U.S. and Japanese steel industry gives several important implications to the Korean steel industry and POSCO. First, continuous cost cutting efforts for maintaining comparative advantage is necessary in today''s competitive environment. Second, POSCO has to pay more attention to technology development and engineering capability through intensive R&D in order to overcome the limitation of quantitative growth. Third, POSCO should apply a win-win strategy for mutual growth with steel consuming industries because supportive demand from the automobile and shipbuilding is absolutely necessary
Thesis(Master) --KDI School:Master of Strategy & International Management,1998